2014
DOI: 10.1016/j.jvs.2014.03.281
|View full text |Cite
|
Sign up to set email alerts
|

Impact of psychological factors on objective ambulatory measures in patients with intermittent claudication

Abstract: Despite equivalent demographic, medical, and psychosocial factors, the type D group was limited in ambulation, suggesting that type D personality is a strong predictor of disease impact in patients with IC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
4
2
2
Order By: Relevance
“…Studies have shown a depressive symptom prevalence of approximately 16% among patients with IC (28). We observed a higher prevalence in our sample (40%).…”
Section: ' Resultscontrasting
confidence: 66%
“…Studies have shown a depressive symptom prevalence of approximately 16% among patients with IC (28). We observed a higher prevalence in our sample (40%).…”
Section: ' Resultscontrasting
confidence: 66%
“…Future research in this area could therefore benefit from utilising more objective measures of health behaviour through the use of a walking pedometer or accelerometer. For example, Torrent et al (2014) showed that Type D personality was associated with less total distance walked during the 6-minute walking test (6MWT) and an increased odds of quitting the 6MWT in patients with peripheral arterial disease. In addition to introducing more objective measures of health behaviour, future research should carry out this study in a cardiac population.…”
Section: Discussionmentioning
confidence: 99%
“…Despite Brazil’s economy changing from agriculture to manufacturing, under governments prior to that of President Bolsonaro, the country has sought to improve environmental sustainability. Several initiatives and programs have been launched to maintain biodiversity and a clean environment, including the creation of Permanent Protection Areas [ 96 ] to surround rivers, and the establishment of the Brazilian Institute of Environment and Renewable Natural Resources, the Special Secretariat of Environment, the National Environmental System, the National Environmental Council, and the Brazilian Institute of Environment and Renewable Natural Resources.…”
Section: Brazilmentioning
confidence: 99%